Effect of pelvic lymph node dissection and its extent on oncological outcomes in intermediate‐risk prostate cancer patients: A multicenter study of the Turkish Uro‐oncology Association. Issue 7 (21st February 2022) - Izol, Volkan; Ok, Fesih; Aslan, Guven; Akdogan, Bulent; Sozen, Sinan; Ozden, Ender; Celik, Orcun; Muezzinoglu, Talha; Turkeri, Levent; Akdogan, Nebil; Baltaci, Sumer
Abstract: Background: Pelvic lymph node dissection (PLND) is the gold standard method for lymph node staging in prostate cancer. We aimed to evaluate the effect of PLND combined with radical prostatectomy (RP) on oncological outcomes in D'Amico intermediate‐risk prostate cancer (IRPC) patients. Methods: Patients with D'Amico IRPC were included in the study. In the overall cohort and subgroups (biopsy International Society of Urological Pathology [ISUP] grade group 2 and 3), patients were divided into two groups as PLND and no‐PLND. More extensive PLND, defined as a number of removed nodes (NRN) ≥ 75th percentile. Results: After exclusion, a total of 631 patients were included: 351 (55.6%) had PLND and 280 (44.4%) had no‐PLND. The mean age was 63.1 ± 3.60 years. The median NRN was 8.0 (1.0–40.0). The mean follow‐up period was 47.7 ± 37.5 months. The lymph node involvement (LNI) rate was 5.7% in the overall cohort, 3.9% in ISUP grade 2, and 10.8% in ISUP grade 3. Patients with PLND were associated with more aggressive clinicopathologic characteristics but no significant difference in biochemical recurrence‐free survival (BCRFS) was found between patients with PLND and no‐PLND ( p  = 0.642). In the subgroup analysis for ISUP grades 2 and 3, no significant difference in BCRFS outcomes was found in patients with PLND and No‐PLND ( p  = 0.680 and p  = 0.922). Also, PLND extent had no effect on BCRFS ( p  = 0.569). The multivariable Cox regression model adjusted for preoperative tumor characteristics revealed that prostate specific antigen (PSA) (HR: 1.18, 95% CI: 1.01–1.25; p  = 0.048) was an independent predictor of biochemical recurrence (BCR). The optimum cut‐off value for PSA, which can predict BCRFS, was assigned to be 7.81 ng/ml, with an AUC of 0.63 (95% CI: 0.571–0.688). The highest sensitivity and specificity were 0.667 and 0.549. Conclusion: Overall and cancer‐specific survival analyzes were not evaluated because not enough events were observed. Neither PLND nor its extent improved BCRFS outcomes in IRPC. The LNI rate is low in patients with biopsy ISUP grade 2 and the BCR rate is low in those with PSA < 7.81 ng/dl so PLND can be omitted in these IRPC patients.